The Infant Intestinal Microbiome: Friend or Foe? - Mshvildadze, Maka (2010)
During the course of mammalian evolution there has been a close relationship between microbes residing in the gastrointestinal (GI) tract and the mammalian host. Interactions of resident intestinal microbes with the luminal contents and the mucosal surface play important roles in normal intestinal development, nutrition and adaptive innate immunity. The GI tract of the premature infant has a large but fragile surface area covered by a thin monolayer of epithelial cells that overlies a highly immunoreactive submucosa. Interactions in the lumen between microbes, nutrients and the intestinal mucosa can range from a healthy homeostasis to an uncontrolled systemic inflammatory response syndrome (SIRS) that leads to multiple organ system failure and death. Recent advances in molecular microbiota analytic methodology that stem from advances in high throughput sequencing technology have provided us with the tools to determine the GI microbiota in great depth, including the nearly 80 % of microbes in the intestine that are very difficult if not impossible to culture by current methodology. Application of these techniques to derive a better understanding of the developing intestinal ecosystem in the premature neonate may hold the key to understand and eventually prevent several important diseases including necrotizing enterocolitis (NEC) and late onset neonatal sepsis that may be acquired via translocation through the GI tract.